Effectiveness of Elephant Grass (Pennisetum purpureum) Green Fertilizer on the Growth of Soybean Plants (Glycine max L. Merrill) - Triyana, Elva; Elfrida, Elfrida; Atmaja, Teuku Hadi Wibowo (Jurnal Biologi Tropis, 2024)
Soybeans (Glycine max L. Merrill) After rice and corn, it is the third most important food commodity and occupies a strategic position in the country's food policy, It plays a very important role in the nutrition of the Indonesian population. The aim of this study was to investigate the effects of soybean plant (Glycine Max). The aim of this study is to investigate the effects of green manure Pennisetum purpureum on plant growth (Merrill). The study was conducted in Batu Melengangan Village, Langkat Regency, using an experimental method involving 2 treatments, namely P0 (without green fertilizers) and P1 (200 grams of green elephant grass fertilizer), and a completely randomized, non-evidence-based design (CRD). In analyzing the data from this study, the SPSS program used parametric tests, i.e. Anova and Duncan tests, and nonparametric tests, i.e. KRUSKAL-Wallis and Mann-Whitney tests. The results of the study show that there was effectiveness of elephant grass green fertilizer (Pennisetum purpureum) on the growth of soybean stem height with an average of 36.25 cm, number of soybean leaves with an average of 46,775 pieces, the age at which soybean flowers emerged with an average of 36.6 days, and the age at which soybeans emerge is an average of 43.2 days. The most effective green manure treatment for the growth of soybean plants (Glycine max L. Merrill) was in treatment P1 (200 gr grass green manure).